STUDENTS’ PERCEPTION TOWARD DIGITAL LITERACY IN LEARNING ENGLISH FOR SPECIFIC PURPOSES (ESP) AT AKPER YPIB MAJALENGKA - Rully Khoeru Solihin (Language and Education Journal, 2023)
Digital literacy competence played an essential role in the growth of university students to achieve their goals of learning. This study was carried out to define the students’ perception of the use of digital literacy in learning English Specific Purposes. The participant consists of the students of the AKPER YPIB Majalengka. 60 students were chosen by purposive sampling technique. The students had a distinctive response regarding the use of digital literacy competence and how they perceive it. This study was a qualitative case study. The data was gathered through open-ended questionnaires and classroom observation. The findings showed that the students had a positive voice regarding the use of digital literacy competence in learning English, they perceived that digital literacy needs willingness and critical thinking skills. Moreover, students’ willingness played a role to find students’ strengths and weaknesses, and students critical thinking skills played an essential to analyze the information and developing their competencies to achieve the learning goals